2019
DOI: 10.1155/2019/9878365
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors Associated with Contagious Caprine Pleuropneumonia in Western Amhara, Northwest Ethiopia

Abstract: Contagious caprine pleuropneumonia (CCPP) has been identified as a significant problem in goat production, especially in the arid and semiarid lowland areas of Ethiopia. Even though CCPP was reported in most of the goat rearing areas of the country, there is no adequate information on the disease in the Amhara Region. Cross-sectional study was conducted from November 2016 to April 2017 in the districts of Western Amhara to estimate the seroprevalence and identify the associated risk factors for occurrence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In the present study, the overall CCPP seropositivity was 45.4%. CCPP has also been reported in some East African countries, including Ethiopia (8.5%) [12] and Uganda (17.7%-23.3%) [31]. In Pakistan, CCPP seroprevalence was reported to be at 32.5% [32].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the present study, the overall CCPP seropositivity was 45.4%. CCPP has also been reported in some East African countries, including Ethiopia (8.5%) [12] and Uganda (17.7%-23.3%) [31]. In Pakistan, CCPP seroprevalence was reported to be at 32.5% [32].…”
Section: Discussionmentioning
confidence: 93%
“…Te present study showed no signifcant diference in PPR and CCPP seropositivity between male and female goats. A higher CCPP seropositivity in females has, however, been reported in Tanzania [38], and this might be because female goats are kept longer for reproduction [12]; their immunity may weaken as they get older, thus increasing their risk of diseases. Univariate analysis revealed no relationship between PPR and CCPP infection despite a 22.3% PPR-CCPP coinfection, and this might be because the two diseases are endemic in the region and the exposure risks are comparable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher prevalence of CCPP in older animals may be attributed to greater exposure to Mccp over a longer period of time and is not necessarily the result of a new infection [ 2 ]. Additionally, reduced physiological status and poor host protection mechanisms in older animals might play an important role in the higher CCPP prevalence compared to younger animals [ 47 ]. The results of this study showed that communal feeding and watering is an important risk factor of CCPP.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that communal feeding and watering is an important risk factor of CCPP. This might be due to the close contact between diseased and healthy animals and, consequently, the circulation of the disease in the population [ 47 ]. The main limitation of the CART model was that the clustering of animals within flocks was not considered.…”
Section: Discussionmentioning
confidence: 99%